Influence of low-intensity light on the biosynthetic activity of the edible medicinal mushroom Hericium erinaceus (Bull.: Fr.) Pers. in vitro - Mykchaylova, Oksana; Dubova, Halyna; Lomberg, Margarita; Negriyko, Anatoliy; Poyedinok, Natalia (Archives of Biological Sciences, 2023)
Paper description: Light is a regulator of the biosynthetic activity of mushrooms but its exact influence remains unclear. An LED matrix-based artificial lighting system was created to study how quasi monochromatic light affects mycelium’s biosynthetic activity. New data on photostimulatory modes of biosynthetic activity in vitro for Hericium erinaceus are presented. Brief exposure of the mycelium to blue and red light wavelength enhanced biosynthetic activity and shortened the cultivation of the investigated strain. Our results enhance erinaceus cultivation biotechnology, boosting process efficiency and yielding more mycelial mass, polysaccharides, and fatty acids as the end product. Abstract: Understanding the impact of light on the physiology and metabolism of edible and medicinal mushrooms can step up the technologies aimed at obtaining bioactive compounds. The article presents data on the influence of low-intensity quasimonochromatic light on the biosynthetic activity of Hericium erinaceus edible medicinal mushrooms in vitro. An artificial lighting setup based on light-emitting diode (LED) arrays with wavelengths λ=470 nm (blue), λ=530 nm (green), and λ=650 nm (red) was used. An argon gas laser served as a coherent visible light source at a wavelength of 488 nm. The mycelium of H. erinaceus irradiation by low-intensity light at wavelengths of 488 nm, 470 nm, and 650 nm reduced the lag phase and increased the culture’s growth rate. The highest biomass yield (12.1 g/L) on the 12th day of cultivation was achieved with light irradiation at a wavelength of 488 nm. Irradiation of the mycelium of H. erinaceus in all used wavelength ranges led to an increase in the synthesis of polysaccharides and unsaturated fatty acids. The modes of irradiation with laser light λ=488 nm and LED λ=470 nm were the most effective.